Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China - Ng, Heok Hee (Zootaxa, 2004)
Pareuchiloglanis macropterus new species, is described from the Salween River (Nujiang) and Irrawaddy River drainages in southern China, and P. rhabdurus new species, is described from the Red River (Song Hong) drainage in northern Vietnam. Pareuchiloglanis macropterus can be distinguished from congeners by the following unique combination of characters: prepelvic length 37.0 42.2% SL; length of adipose-fin base 31.8 37.0% SL (dorsal-fin base 3.3 3.5 times in adipose-fin base); caudal peduncle length 17.6 20.0% SL; caudal peduncle depth 6.8 7.4% SL (2.4 3.0 times in caudal peduncle length); body depth at anus 9.5 12.6% SL; snout length 50.3 56.5% HL; interorbital distance 24.6 30.2% HL; 41 42 vertebrae; pectoral fin reaching to pelvic-fin origin; ventral limit of gill opening to level of third or fourth pectoral-fin element; posterior base of adipose fin notched and separate from caudal fin; and presence of pale patches on body. Pareuchiloglanis rhabdurus can be distinguished from congeners chiefly by a slender body (8.7% SL) and caudal peduncle (4.2% SL; 4.2 times in caudal peduncle length), as well as a combination of the following characters: length of adipose-fin base 34.7% SL; dorsal to adipose distance 12.2% SL; caudal peduncle length 17.6% SL; snout length 57.0% HL; interorbital distance 25.5% HL; adipose and caudal fins separate; and ventral limit of gill opening to base of first pectoral-fin element.